Scuba Diving Fatalities in Istanbul - Güven, Aykut Taner; Şam, Bülent; Şirin, Gözde (The Bulletin of Legal Medicine, 2004)
Scuba (self contained underwater breathing apparatus) diving as a water recreation and sporting activity has become immensely popular in recent years in Turkey, with almost thirty thousand certified and non-certified divers. Although serious injuries occur infrequently, evident increase in diver deaths were also reported parallel to the increasing number of scuba divers. The incidence of scuba diving related deaths in routine autopsy practice is rare.All autopsies performed at Council of Forensic Medicine in Istanbul, between 1995-2001 were reviewed and data was collected retrospectively. We have found just 3 cases over in this period. In conclusion, scene investigation data were not transmitted adequately to the physician who performs the autopsy. Therefore origin of the lesions determined by external and internal examination cannot be illuminated definitely, so the cause and mechanism of death remains unclear. Key words: Forensic autopsy, scuba diving fatalities, air embolism, barotrauma, decompression sickness.